Solar photocatalytic activity of anatase TiO2 nanocrystals synthesized by non-hydrolitic sol–gel method - Leong, K.H.; Monash, P.; Ibrahim, S.; Saravanan, P. (Elsevier, 2014)
Nanocrystalline anatase TiO2 was prepared through modified non-hydrolitic sol–gel method by reacting TiCl4 with benzyl alcohol at room temperature. The as synthesized anatase TiO2 was calcined at 450 °C for 5 h. The size and morphology of the as synthesized and calcined TiO2 nanoparticles were characterized using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM) and BET surface area analysis. The band gap energy was measured using Kulbeka-Munk function and the electronic state of the prepared TiO2 was determined by X-ray photoelectron spectroscopy (XPS). The photocatalytic activity of the prepared samples was investigated by degrading 50 mg/L of 2,4-dichlorophenol (2,4-DCP) under natural sunlight as a source of irradiation. The obtained XRD patterns of both as synthesized and calcined TiO2 matches completely with the tetragonal anatase phase of TiO2. The as synthesized sample showed higher surface area (147.34 m2/g) with particles size ranging between 3 and 6 nm than the calcined titania (64.92 m2/g) of prarticle size ranging between 11 and 15 nm. Both the TiO2 samples showed excellent photocatalytic activity for the degradation of 2,4-DCP under natural sunlight irradiation. The complete removal of 2,4-DCP is obtained after 2.5 h for calcined TiO2 and 3.5 h for as synthesized TiO2 suggests that the prepared photocatalysts have the potential to degrade the organic pollutants. The degradation of 2,4-DCP followed first order kinetics.